PENGARUH BELANJA ONLINE DAN OFFLINE TERHADAP PERILAKU KONSUMEN (STUDI EMPIRIK PADA MAHASISWA PRODI PENDIDIKAN EKONOMI FAKULTAS EKONOMI DAN BISNIS) - Rohmadhonawati, Wita Nur; Irmayanti, Elis; Afandi, Tjetep Yusuf (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine whether online and offline shopping affect consumer behavior. The study used a descriptive quantitative approach. Collecting data from 60 respondents with purposive sampling technique using a questionnaire. Data analysis using SPSS version 24, namely instrument testing, basic assumptions, multiple linear regression, determination, and hypotheses. The significant value of the t test of online and offline shopping on consumer behavior is: online shopping is 0.00 < 0.05 with t count 6.060 > t table 2.002, and offline shopping is 0.00 < 0.05 with t count 6.241 > t table 2.002 . The significant value in the f test of online and offline shopping on consumer behavior is 0.00 < 0.05 with an f count of 70.490 > 3.16. Conclusion (1) there is a positive and significant influence between online shopping on consumer behavior. (2) there is a positive and significant effect between offline shopping on consumer behavior. (3) there is a positive and significant influence on online and offline shopping on consumer behavior